Pengembangan Materi Ajar pada Teks Ulasan Film Berbasis Microsoft Powerpoint Interaktif pada Siswa Kelas VIII SMPN 35 Medan Tahun Ajaran 2022/2023 - Esra Romauli Berutu; M. Joharis Lubis (FKIP, Universitas Palangka Raya, 2024)
The purpose of this study was to determine the process and feasibility of developing interactive Microsoft PowerPoint-based film review text material for Grade VIII students at SMPN 35 Medan. The approach employed is the method of research and development (Research and Development/R&D). Sugiyono has modified the research method with a design according to the needs and limitations of this study. The researcher then simplified it into six stages, namely: (a) potential and problems, (b) data collection, (c) product design, (d) product validation, (e) product revision, and (f) testing of respondents. The feasibility value of a product can can be assessed using a Likert scale based on the validation outcomes provided by experts in the field of content and media..The process of developing this material was carried out to add some of the contributions of existing material to make even better film review text material. T The outcomes revealed that the product emanating from the study